Confronting Islamophobia and its consequences in East London in a context of increased surveillance and stigmatisation. (February 2023) - Balazard, Hélène; Peace, Timothy
Islamophobia is an issue faced by Muslims across Europe. In the UK, there is a growing acceptance that the government's counter-terrorism policy, Prevent, has led to increased discrimination. Current research is split on whether discrimination among Muslims is leading to disengagement and a retreat from public life or whether this has inspired a feeling of responsibility to participate more actively and engage in politics or alternative forms of political resistance. This paper presents the results from the London case study of a larger comparative project which seeks to assess the political consequences of the experience of discrimination by evaluating the individual and collective responses of Muslims in terms of political participation and representation. Based on qualitative research including semi-structured interviews and participant observation in Tower Hamlets (East London), we show how Muslim individuals, including civil society actors, have responded to Islamophobia, and the discrimination associated with it, in a context of increased surveillance after the introduction of the 'Prevent Duty' in 2015. We focus on individual responses to confronting discrimination and stigmatisation and include a case study of an initiative by the campaigning group Citizens UK which sought to explore the potential for collective responses and wider coalitions against discrimination faced by Muslims. We investigate the emerging strategies that are being adopted as a reaction to discrimination and examine the extent to which responses constitute a means of 'fighting back' through political participation and engagement and whether this new climate has fostered either mobilisation or demobilisation. Our findings indicate that individual forms of resistance are more prominent than mass mobilisation and some evidence of Muslims retreating from political engagement.